Geography’s ‘Decolonial Turn’? A Conversation between Lindsay Naylor and Tariq Jazeel - Naylor, Lindsay; Jazeel, Tariq (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
This piece is an edited transcript of a conversation on decolonizing Geography that took place between Lindsay Naylor and Tariq Jazeel in February 2024 in response to the ACME 20+ year anniversary celebrations. As decolonial theory and efforts around decolonizing geography continue to gain momentum, this conversation – between two differently located geographers – reflects on the trajectories, geographies, meanings and (institutional) politics of decoloniality as it has taken shape across the discipline. From their own experience and vantage points, Naylor and Jazeel consider the past, the promise, and the potential of decoloniality for Geography.